The Influence of Online Games on Sleep Quality in Adolescent Males in Lina Ino Village, Central Tobelo District - Yurensi Felni Tjingaisa; Devetsus Kitong (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
This research has a goal for to determine the effect of online games on sleep quality in adolescents in Lina-Ino Village, Tobelo Tengah District. This research uses quantitative methods with a predictive/influence research design. There are 160 adolescents taken as samples in this research using the simple random sampling technique. Data collected using a questionnaire. The result of this research of statistical tests showed an effect of online games on sleep quality (P value 0.000). This result show the impact of online gaming on adolescents in Lina-Ino Village, indicating that the majority of adolescents fall into the category of always playing online games (55%). The sleep quality of adolescents in Lina-Ino Village shows that the majority of adolescents have poor sleep quality (67%). There is a significant influence (90%) between online gaming and sleep quality in Lina-Ino Village. Suggestions for adolescents include being wiser and firmer in setting time limits for online gaming, so that the use of this technology remains useful as a form of entertainment and does not negatively impact adolescent development and health. Parents are also expected to build better communication and relationships with adolescents and create activities within the family to encourage children to be more active and develop their thinking, rather than allowing them to sit for hours playing online games.